Harmonic mappings related to Janowski starlike functions - Kahramaner, Yasemin; Aydoğan, Melike; POLATOĞLU, YAŞAR (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2014)
The main purpose of the present paper is to give the extent idea which was introduced by Robinson(1947) [6]. One of the interesting application of this extent idea is an investigation of the class of harmonic mappings related to Janowski starlike functions. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Harmonic mappings; Distortion theorem; Growth theorem; Coefficient inequality